"Não é uma caixa!":uma análise das vivências das crianças na atividade de brincar ao longo de três anos - Jacqueline da Silva Gonçalves (2024)
This research aims to understand the processes of imagination and creation in children from infancy, specifically during play activities, at the Municipal School of Early Childhood Education (EMEI) Tupi in Belo Horizonte, Brazil, from 2017 to 2019. The theoretical and methodological approach combines Historical-Cultural Theory and Ethnography in Education. Within the framework of Historical-Cultural Theory, imagination is conceptualized as a higher psychological function (developing in connection with other psychological functions), and creation as a product of imagination. We consider play activities as the locus of imagination and creation, where children explore, experiment, and engage with the historical-cultural reality in which they are embedded. In the context of Educational Ethnography, EMEI Tupi is seen as a place where culture unfolds and transforms into extraordinary events. The abductive logic employed in this study serves as a sign of difference between the researcher’s perspective and what is happening in the moment under analysis—essentially asking, ‘What is happening there?’ Additionally, the ethnographic principle of contrast involves examining the various languages in use, speech patterns, actions, and expressions of participants within a social group, along with their diverse interpretations of these actions and events. The empirical material is drawn from the EnlaCEI/UFMG Research Group’s database, compiled by researchers between 2017 and 2019. This database includes field notes, film records, and photographs from EMEI Tupi. Microgenetic analysis was conducted on four selected events: ‘Not a Box!’ (02/14/2019), ‘Larissa’s Crib/Bathtub’ (03/26/2019), ‘Little Train’ (08/12/2019), and ‘Rita’s Little House’ (09/30/2019). We argue that in these analyzed events, where we prioritize the imaginary situations experienced by children, the pivotal object—the cardboard box—is transformed (through words, gestures, actions), assuming different configurations in the shared [imagination/creation] process. Through the unit of analysis of shared [imagination/creation], children reveal the process of signification. The meanings attributed to the cardboard box and other objects have their origins in the interplay between collective life experiences and the individual and affective dimensions of the children. Thus, we propose that children create imaginary situations during play, and their experiences—both within the family and educational institution—can trigger new possibilities of [imagination/creation], dialectically promoting their cultural development.